Unlocking the Therapeutic Potential of Patchouli Leaves: A Comprehensive Review of Phytochemical and Pharmacological Insights - Isack Ibrahim Mrisho; Elshan Musazade; Haobo Chen; Huixuan Zhao; Junjia Xing; Xue Li; Jiahong Han; Enbo Cai (Plants)
Plant-based products play an increasingly vital role in the pharmaceutical industry, including Pogostemon cablin (Blanco) Benth. (patchouli), which is notable for its rich history and extensive use in traditional medicine. Patchouli has a longstanding historical use as a remedy for a wide range of health conditions, including colds, fevers, headaches, inflammation, digestive disorders, and insect and snake bites. Comprehensive phytochemical studies have revealed that patchouli leaves contain diverse valuable bioactive compounds, notably patchouli alcohol, β-patchoulene, pogostone, α-bulnesene, and β-caryophyllene. Recent studies have demonstrated that patchouli leaves exhibit various pharmacological properties, including anti-oxidant, anti-inflammatory, antimicrobial, antidepressant, and anticancer effects. Despite robust traditional knowledge, specific therapeutic applications of patchouli leaves require scientific validation and standardization of their bioactive compounds. This review provides a comprehensive overview of the existing literature on the phytochemical composition, pharmacological properties, and underlying mechanisms of action of patchouli essential oil (PEO) and plant extracts obtained from patchouli leaves. It offers detailed insights into potential therapeutic applications, aiming to inform and guide future research across multiple medical disciplines. Ultimately, this review underscores the need for further research to validate and develop the medicinal applications of patchouli leaves, providing a foundation for future healthcare advancements.